(untitled) (Research, Society and Development, 2021)
Objective: To understand the activation of the ECA II / Ang 1-7 / Receptor Mas route as a pharmacological target in cardiac pathologies. Methodology: This is a systematic literature review, researched in the EMBASE, MEDLINE and SCIELO databases, which used the PRISMA protocol to extract primary data and transform it into secondary data. Results: The Renina Angiotensin System is an essential component for the proper physiological functioning and homeostasis of the cardiovascular system. Being divided into two axes, the classic, which is currently used in the pharmacotherapy of hypertension and cardiovascular diseases. It is the non-classical axis that, via the angiotensin II converting enzyme (ACE II), angiotensin (1-7) and Mas receptor pathway, has demonstrated an important vasodilator and cardioprotective effect. They demonstrate a promising outcome and reinforce the effective action of MasR as a vasodilator, cardioprotection and reduction of myocardial remodeling. Final Considerations: The non-classical axis has potential in the development of drugs to expand new pharmacological strategies for cardiovascular diseases.